A PANORAMIC COMPARISON ON CORPORATE SOCIAL RESPONSIBILITY LAW 2013 AND COMPANIES AMENDMENT ACT 2019 TO SUSTAINABLE DEVELOPMENT GOALS ACT IN INDIA - Ms. Aishwarya; S Vethirajan. C (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Corporate social responsibility (CSR) is the level of commitment extended by businesses towards society in terms of sustainable practice. The proliferation of societal needs is a trending global agenda to corporates. This article will attempt to trace the history of CSR since its inception. This paper will also encompass discussions on the CSR law that was framed in 2013 and the amended CSR act in 2019. In addition, this study will evaluate, compare and contrast the CSR laws with that of (SDG) Sustainable development goals. This article will also capture the interface between CSR and SDGs.